2012
DOI: 10.2516/ogst/2012004
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Inversion of Production Data and Seismic Attributes: Application to a Synthetic SAGD Produced Field Case

Abstract: Résumé -Inversion simultanée des données de production et des attributs sismiques : application à un champ synthétique produit par injection de vapeur -L'utilisation conjointe des données de production et des attributs de sismique répétée facilite la compréhension des mouvements de fluide dans les formations géologiques et aide à la construction de modèles numériques fiables représentant ces formations. Ceci a récemment motivé le développement de techniques d'inversion ou de calage dédiées à l'identification d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…The evolutionary algorithm is based on the notion of Darwinian evolution, it deals with concepts such as selection, recombination and mutation, and it is often used for reservoir history matching (Bäck, 1996, Soleng, 1999, Romero et al, 2000, Williams et al, 2004, Schulze-Riegert and Ghedan, 2007. In history matching, the termination criteria is usually until the objective function is small enough, convergence is obtained, or the number of iterations exceeds a maximum value (Tillier et al, 2012). The termination criteria used in this work is the convergence criteria.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The evolutionary algorithm is based on the notion of Darwinian evolution, it deals with concepts such as selection, recombination and mutation, and it is often used for reservoir history matching (Bäck, 1996, Soleng, 1999, Romero et al, 2000, Williams et al, 2004, Schulze-Riegert and Ghedan, 2007. In history matching, the termination criteria is usually until the objective function is small enough, convergence is obtained, or the number of iterations exceeds a maximum value (Tillier et al, 2012). The termination criteria used in this work is the convergence criteria.…”
Section: Methodsmentioning
confidence: 99%
“…The corresponding characteristics of these data aid in obtaining realisitic models of the reservoir through a seismic assisted history matching scheme. History matching is considered an inverse problem (Kretz et al, 2004, Tillier et al, 2012, it is a process of simultaneously perturbing reservoir parameters such that it can be represented as a minimization problem where observed dynamic data are used to condition reservoir models by reducing the misfit between the observed data and model predicted data through an objective function. The use of the conventional least squares formulation for computing production data objective function and misfit has been shown to be suitable and efficient (Oliver and Chen, 2011), such that it can be significantly reduced during the history matching process, and properly characterizes the error between the simulated data and the real data (Tillier et al, 2013); hence this approach is used in this work.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The so-obtained value is incorporated into the objective function as the seismic mismatch term. Tillier et al (2012) proved the efficiency of this approach for conditioning a synthetic SAGD operated field case.…”
Section: Objective Functionmentioning
confidence: 99%
“…Several research papers showed that the least-square formulation was not relevant for quantifying the seismic mismatch (Aanonsen et al, 2003;Roggero et al, 2012). Tillier et al (2012) suggested a different metric called Local Dissimilarity Map (LDM). The leading idea is to evidence meaningful features instead of exactly matching seismic data in every grid blocks.…”
Section: Objective Functionmentioning
confidence: 99%